Ответ:
-1 - (-x) = 3 - 4×(10 ÷ 2|5)
-1 + x = 3 - 4×(10 ÷ 5)
-1 + x = 3 - 4×2
-1 + x = 3 - 8
Тепер скоротимо константи:
x - 1 = -5
І додамо 1 до обох частин рівняння:
x - 1 + 1 = -5 + 1
Отримаємо:
x = -4
Відповідь: x = -4.
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-1 - (-x) = 3 - 4×(10 ÷ 2|5)
-1 + x = 3 - 4×(10 ÷ 5)
-1 + x = 3 - 4×2
-1 + x = 3 - 8
Тепер скоротимо константи:
x - 1 = -5
І додамо 1 до обох частин рівняння:
x - 1 + 1 = -5 + 1
Отримаємо:
x = -4
Відповідь: x = -4.
Пошаговое объяснение: